Biodegradable Cellulose Film Prepared From Banana Pseudo-Stem Using an Ionic Liquid for Mango Preservation - Ai, Binling; Zheng, Lili; Li, Wenqi; Zheng, Xiaoyan; Yang, Yang; Xiao, Dao; Shi, Jian; Sheng, Zhanwu (Frontiers in Plant Science, 2021)
The excessive use and disposal of plastic packaging materials have drawn increasing concerns from the society because of the detrimental effect on environment and ecosystems. As the most widely used fruit packing material, polyethylene (PE) film is not suitable for long-term preservation of some tropical fruits, such as mangos, due to its inferior gas permeability. Cellulose based film can be made from renewable resources and is biodegradable and environmental-friendly, which makes it a promising alternative to PE as a packaging material. In this study, cellulose film synthesized from delignified banana stem fibers via an ionic liquid 1-Allyl-3-methylimidazolium chloride ([AMIm][Cl]) were evaluated as packing material for mangos preservation. The moisture vapor transmission rate and gas transmission rate of the synthesized cellulose film were 1969.1 g/(m2·24 h) and 10015.4 ml/(m2·24h), respectively, which are significantly higher than those of commercial PE films. The high permeability is beneficial to the release of ethylene so that contribute to extend fruit ripening period. As a result, cellulose film packaging significantly decreased the disease and color indexes of mangos, while prolonged the storage and shelf life of marketable fruits. In addition, the cellulose film was decomposed in soils in 4 weeks, indicating an excellent biodegradability as compared to the PE plastic film.